A new multipurpose diffractometer PILATUS@SNBL. (1st April 2016) - Dyadkin, Vadim; Pattison, Philip; Dmitriev, Vladimir; Chernyshov, Dmitry
Abstract : A new multifunctional diffractometer based on the Dectris Pilatus 2M detector has been constructed, commissioned and offered to users. The diffractometer combines a fast and low‐noise area detector together with flexible goniometry for sample and detector positioning and orientation. Abstract : The diffraction beamline BM01A at the European Synchrotron Radiation Facility (CRG Swiss–Norwegian beamlines) has been successfully operational for 20 years. Recently, a new multifunctional diffractometer based on the Dectris Pilatus 2M detector has been constructed, commissioned and offered to users. The diffractometer combines a fast and low‐noise area detector, which can be tilted and moved horizontally and vertically, together with flexible goniometry for sample positioning and orientation. The diffractometer is controlled by a user‐friendly and GUI‐based software Pylatus which is also used to control various auxiliary equipment. The latter includes several heating and cooling devices, in situ cells and complimentary spectroscopic tools.